Study of relationship of structural and steam curing characteristics in nanostructured binder based foam concrete - N. V. Pavlenko; P. P. Pastushkov; A. N. Kharkhardin; E. V. Voitovich (Вестник СибАДИ)
In the paper the results of steam curing characteristics in nanostructured binder based foam concrete and their comparison with analogues are presented. Also the comparison study of parameters of vapor permeability,sorption hymidity,capillarity rise, heat conductivity (in dry service conditions) is realized. Effect of cellular composite structure on properties and reinforcement process of foam concrete is studied.